PERANAN DINAS KOPERASI DAN UMKM KOTA JAMBI DALAM PEMBERDAYAAN UMKM KULINER DI KECAMATAN KOTA BARU - Nurshakila; Sissah; Victor Diwantara (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research entitled The Role of Dinas Koperasi dan Usaha Mikro Kecil Menengah of Jambi City in Empowering the Culinary Business Sector in Kota Baru District. This study using qualitative research methods. The types and sources of data are primary data and secondary data. Data collection techniques were carried out by means of observation, interviews and documentation, while data analysis methods included data collection, data reduction, data presentation and conclusions. The result of this study is the empowerment from related goverment parties to SME owners mostly has been evenly distributed, but there are several things don't get attention. The advices are Dinas Koperasi and SME Jambi City expected to improve their performance in supporting SME empowerment, to be consistent in the role of empowering and developing businesses, and to find the innovations of friendly business for SME owners